The currency and financial system of mainland China - Miyashita, Tadao; Ajia Keizai Kenkyūjo (Japan) (Seattle: University of Washington Press, 1966)
This book is a study of the currency system of China, centred on the People's Currency, and of the mechanisms of the Chinese financial system, centred on the People's Bank of China.
At head of title: Institute of Asian Economic Affairs.
Includes index
Bibliography: p. [249]-257.
usc 30/10/18
Loans
Keywords: Currency question; Finance; Financial system; China